Dimensions of the lived experiences of doctoral students in South Africa - Moodley, Padhma (African Perspectives of Research in Teaching & Learning (APORTAL), 2022)
Students engage in their postgraduate studies with an accumulation of experience and knowledge. The autonomy and independence that postgraduate studies call for represent a drastic shift from the norms that students are accustomed to. This study examined the dimensions of the lived experiences of doctoral students in South Africa which influence their independence and autonomy. The importance of this study resides in its examination of the multiplicity of challenges that doctoral students experience throughout their journey, as identified through the various dimensions of their lived experiences. The contribution of this study is relevant to the reflection on extant practices of postgraduate engagement at universities in S.A.The participants in this study comprised a convenience sample of seven postgraduate students currently registered for their PhD qualification. Data was gathered using an openended self-reporting questionnaire. Through a content analysis, several themes emerged such as personal development, group engagement, and the role of the supervisor. The study’s findings underscore the need for a more comprehensive and supportive approach towards doctoral students in South Africa. It is recommended that whilst doctoral students engage independently in their studies, there is need for the institution to provide scaffolding support across the dimensions this study identified
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 6 (3) (2022) Special Issue
Keywords: Lived Experience; Peer Support; Personal Issues; Phenomenological Study; Postgraduate; Supervisor Support; Phenomenological psychology; Graduate students; College students -- South Africa